2022
DOI: 10.3171/2022.2.spine2281
|View full text |Cite
|
Sign up to set email alerts
|

Segmental range of motion after cervical total disc arthroplasty at long-term follow-up: a systematic review and meta-analysis

Abstract: OBJECTIVE As an alternative procedure to anterior cervical discectomy and fusion, total disc arthroplasty (TDA) facilitates direct neural decompression and disc height restoration while also preserving cervical spine kinematics. To date, few studies have reported long-term functional outcomes after TDA. This paper reports the results of a systematic review and meta-analysis that investigated how segmental range of motion (ROM) at the operative level is maintained with long-term follow-up. METHODS PubMed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…A recent systematic review and meta-analysis shows that sROM initially improves after ACDA, but at the long-term (average of 5-years), sROM diminishes back to values similar to those preoperatively, which is in line with our findings ( Zavras et al, 2022 ). A recent publication by Wu et al also demonstrated that ROM increases after ACDA in younger patients, but decreases in elderly patients after 2 years ( Wu et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…A recent systematic review and meta-analysis shows that sROM initially improves after ACDA, but at the long-term (average of 5-years), sROM diminishes back to values similar to those preoperatively, which is in line with our findings ( Zavras et al, 2022 ). A recent publication by Wu et al also demonstrated that ROM increases after ACDA in younger patients, but decreases in elderly patients after 2 years ( Wu et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…An REE greater than 2 mm increases the chance of developing grade three or four HO, which accelerates the degeneration of adjacent segments. Although inferior-segment degeneration rates are equally prevalent in both cTDR and ACDF cases, superior-segment degeneration rates are not [ 9 , 10 ]. Some studies have found that HO is less prevalent in multilevel cTDR than in single-level procedures at a two-year follow-up, while others have found no significant differences [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported that ROM may decrease owing to heterotropic ossification, mechanical malfunction of the device, or implant wear. As a result of comparing several studies, Hence, Zavras et al [ 73 ] reported that ROM immediately postoperatively improved compared to ROM preoperatively, and no significant change in follow-up up to 1 year was observed. However, in the long-term follow-up (average, 99.86 months), the ROM deteriorated significantly, and efforts to maintain a good long-term ROM were necessary [ 73 ].…”
Section: Cervical Disc Replacementmentioning
confidence: 99%